Analisis Keterlambatan Proyek Pembangunan Gudang dengan Precedence Diagram Method (PDM) dan Program Evaluation and Review Technique (PERT) - Putra Chandra Rachmat Alim; Reno Pratiwi; Suheriah Mulia Devi (Jurnal Talenta Sipil, 2026)
Construction project delays are a common issue that significantly affect cost, quality, and completion time. This condition occurred in the construction of the PT Telkom Closed Warehouse in Balikpapan, which was originally planned to be completed within 90 calendar days but experienced a 28-day delay, resulting in a total completion time of 118 days. The delay was mainly caused by weak supervision and the absence of a structured planning method from the beginning. This study aims to analyze critical activities using the Precedence Diagram Method (PDM) and to calculate the probability of project completion using the Program Evaluation and Review Technique (PERT). The analysis results indicate that concrete structure work, wall installation, flooring, roofing, and mechanical-electrical work were identified as critical path activities. In addition, the PERT method provided an overview of the probability of achieving the actual project schedule. The conclusion of this research emphasizes that the application of PDM and PERT can help contractors plan schedules more accurately, reduce the risk of delays, and optimize the use of project resources.